Technology and Demand for Skilled Labor in Turkish Private Manufacturing Industries - Aksoy, Tolga (Panoeconomicus, 2009)
This paper examines the relationship between technology and demand for skilled labor both historically and empirically. First, it is pointed out that the Industrial Revolution substituted skilled labor with unskilled labor since it has a de-skilling characteristic. Second, the skill-bias feature of Information and Communication Technologies Revolution is suggested. Finally, the effect of technological progress on the demand for skilled labor is tested for Turkish Private Manufacturing Industries. According to the static panel data estimation results, there is a positive but weak relationship between technological progress and demand for skilled labor. Key words: Skill bias, Technological change, Manufacturing. JEL: O33, J23, J24.